Fluorescence energy transfer dye-labeled primers for DNA sequencing and analysis. - Ju, J (1995)
Fluorescent dye-labeled DNA primers have been developed that exploit fluorescence energy transfer (ET) to optimize the absorption and emission properties of the label. These primers carry a fluorescein derivative at the 5' end as a common donor and other fluorescein and rhodamine derivatives attached to a modified thymidine residue within the primer sequence as acceptors. Adjustment of the donor-acceptor spacing through the placement of the modified thymidine in the primer sequence allowed generation of four primers, all having strong absorption at a common excitation wavelength (488 nm) and fluorescence emission maxima of 525, 555, 580, and 605 nm. The ET efficiency of these primers ranges from 65% to 97%, and they exhibit similar electrophoretic mobilities by gel electrophoresis. With argon-ion laser excitation, the fluorescence of the ET primers and of the DNA sequencing fragments generated with ET primers is 2- to 6-fold greater than that of the corresponding primers or fragments labeled with single dyes. The higher fluorescence intensity of the ET primers allows DNA sequencing with one-fourth of the DNA template typically required when using T7 DNA polymerase. With single-stranded M13mp18 DNA as the template, a typical sequencing reaction with ET primers on a commercial sequencer provided DNA sequences with 99.8% accuracy in the first 500 bases. ET primers should be generally useful in the development of other multiplex DNA sequencing and analysis methods.